2005
DOI: 10.1207/s15328023top3203_3
|View full text |Cite
|
Sign up to set email alerts
|

Using Student Journals to Stimulate Authentic Learning: Balancing Bloom's Cognitive and Affective Domains

Abstract: Bloom (1956) pioneered the measurement of learning outcomes with a taxonomy of educational objectives, but educators often ignore affective learning objectives and focus on attaining cognitive objectives. This study examined student journals as a way to correct the overemphasis on cognitive objectives. Results suggested that course expectations and affective journal outcomes were important correlates of student evaluations of course outcomes even after controlling for the instructor, student gender, and stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…This has evolved into a more recent interest and tendency for diaries and journals to be used as part of a much wider reflexive meta-cognitive strategy to assist students in understanding their ability to transform their own learning strategies whilst in study at university, and subsequently (and possibly controversially-see for example Crème 2005) to link these with attainment levels, the diaries themselves being used for both assessment and predictive grading purposes (Hyers 2001;Hui-fang 2005). Research in the fields of diaries and journaling has demonstrated that prospective and dynamic writing, in contrast with retrospective writing, may well increase the validity of students' assessment of their work and can highlight the powerful role of the teacher in interpreting formal assessment 'discourses' (Thornbury 1991;McCrindle & Christensen 1995;Bolin et al 2005). Further, emerging research (Struyven et al *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…This has evolved into a more recent interest and tendency for diaries and journals to be used as part of a much wider reflexive meta-cognitive strategy to assist students in understanding their ability to transform their own learning strategies whilst in study at university, and subsequently (and possibly controversially-see for example Crème 2005) to link these with attainment levels, the diaries themselves being used for both assessment and predictive grading purposes (Hyers 2001;Hui-fang 2005). Research in the fields of diaries and journaling has demonstrated that prospective and dynamic writing, in contrast with retrospective writing, may well increase the validity of students' assessment of their work and can highlight the powerful role of the teacher in interpreting formal assessment 'discourses' (Thornbury 1991;McCrindle & Christensen 1995;Bolin et al 2005). Further, emerging research (Struyven et al *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Authentic activities provide the opportunity to reflect 7. Authentic activities can be integrated and applied Against all the characteristics written upwards, researchers accentuate that it is impossible to design truly 'authentic' learning tasks and there has been a great deal of written about the differences between the tasks and problems that we face in real-world and in schools [18], [41].…”
Section: "Learners Need To Have Opportunities To: Explore a Situationmentioning
confidence: 99%
“…This structure aims to classify students' learning outputs and achieving togetherness by assessing their achievements with the same assessment tool (Krathwohl, 2002). Bloom and his colleagues can be accepted as the first pioneers of evaluation of learning outputs through the taxonomy of detailed educational objectives (Bolin, Khramtsova and Saarnio, 2005).…”
Section: Theoretical Framework Cognitive and Affective Objectives In mentioning
confidence: 99%